Értékorientált vezetőképzés a református köznevelés szolgálatában - SZONTAGH, Pál Iván (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
Value-Driven Training of Leaders in the Service of Reformed Public Education. Our paper focuses on a specific subsystem of the Hungarian public education system, the Reformed educational network. After a theoretical foundation, the study will review the characteristics and legislative environment of Reformed public education management and leadership training, and then examine the concept, reception, results, and further development potentials of the accredited training in Value-Driven Leadership, a relatively new element of the range of trainings. Some basic conclusions can be drawn from the survey as: (1) The target group is very interested in modern knowledge about Christian leadership, which is considered a priority area, which also coincides with the needs of the maintenance. (2) The management powers of headmasters of ecclesiastical institutions are much broader than those of headmasters of public institutions, but their knowledge and interest in these areas are insufficient. (3) More than ever before, the organization of training should aim at modularity and a variety of organizational methods.